Determination of Curve Number for the Temef Watershed, Timor Tengah Selatan Regency - Welkis, Davianto Frangky; Harisuseno, Donny; Wahyuni, Sri; Beselly, Sebrian Mirdeklis (Fakultas Teknik, Universitas Brawijaya, 2023)
This study aims to show that the Curve Number (CN) method can represent the relationship between rainfall runoff in the Temef Watershed, an area of ​​East Nusa Tenggara. The method used in this study was quantitative analysis by linking watershed characteristics such as soil, vegetation, and land use with the CN curve number, which shows the potential flow for a certain rainfall. CN data were re-analyzed using a computer program to obtain actual field conditions, which were then classified to obtain land cover quality, soil type, CN value, and Antecedent Moisture Condition (AMC) value for the Temef Watershed. Based on the study's results, it was found that the Temef Watershed was dominated by secondary dry land forest cover, which ranged from 28.50-52.00%. The lithological texture of rocks in the Temef Watershed is dominated by conglomerate and gravel with a gradation rate from medium to high; sandy marl, sandstone, tuft, and dacite of medium to a high gradation; and scaly clay with very low to low gradation. The CN value is 69.45, classified as medium gradation at normal soil moisture levels. The benefits of this result include the practical application of the CN method, the provision of accurate field conditions through re-analysis, insights into dominant land cover and lithological texture, and the establishment of CN values for effective water resource management.